The methodology of using illustrative cites in Webster’s Dictionary - Taouririt, Houssem eddine; Ali zerouki, Abdelkader (Journal of Human Sciences, 2021)
This present research addresses the methodology of presenting quotes in "webster’s third international dictionary" and the reality of the existence of illustrative quotations. And all the data accompanying the editing process and had a direct role in determining how the editorial team dealt with this lexicon component. As well as the controversy over the level of the language of citations and sources of citation and who can we quote from, the timeframe of citations, and the identity crisis in selecting the linguistic content of the dictionary.